2011
DOI: 10.1145/2036264.2036273
|View full text |Cite
|
Sign up to set email alerts
|

Fair Seeding in Knockout Tournaments

Abstract: We investigated the existence of fair seeding in knockout tournaments. We define two fairness criteria, both adapted from the literature: envy-freeness and order preservation. We show how to achieve the first criterion in tournaments whose structure is unconstrained, and prove an impossibility result for balanced tournaments. For the second criterion we have a similar result for unconstrained tournaments, but not for the balanced case. We provide instead a heuristic algorithm which we show through experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…A comprehensive analysis of knockout tournaments is proposed in [3,4]. Traditionally, the method for designing a tournament involves two stages: (i) tournament structure design and (ii) seeding.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive analysis of knockout tournaments is proposed in [3,4]. Traditionally, the method for designing a tournament involves two stages: (i) tournament structure design and (ii) seeding.…”
Section: Related Workmentioning
confidence: 99%
“…An important aspect concerns the factors that can be used to evaluate a tournament design. This problem has been also considered in previous works [3,4]. An interesting discussion of economic aspects of tournament attractiveness, such as spectator interest, is provided by [7].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…He proves that the canonical knockout bracket fails to satisfy the second axiom and suggests a variant that satisfies all three seeding axioms, in which subgroups of teams are randomly shuffled. Vu and Shoham (2011) introduce two alternative criteria for fairness (envy-freeness and order preservation) and investigate several impossibility results. Karpov (2015) develops an axiomatic theory of knockout tournaments, gives axiomatic justification for various seedings methods, suggests two new seeding methods (equal gap seeding and increasing competitive intensity seeding), and provides many useful references.…”
Section: Remarkmentioning
confidence: 99%
“…In the deterministic case Lang et al investigate the problem of setting an agenda for a sequential majority vote (identical to scheduling match-ups in a caterpillar tournament) such that a particular outcome wins [30]. Vu et al initiated the investigation of the question of setting the schedule, subject to various sets of constraints on fairness and interesting-ness, often finding the problems computationally hard [51][52][53]. Williams found that, for certain dominant entrants in a cup tournament it is easy to find a schedule such that a particular entrant will win [56].…”
Section: Related Workmentioning
confidence: 99%